Accounting conservatism and corporate cross- listing: The mediating effect of the corporate governance - Mouna M'rad (Cogent Economics & Finance, 2022)
The purpose of this paper is to investigate the relationship between accounting conservatism and companies' cross- listing decision and the mediating role of the corporate governance mechanisms: board of directors' characteristics and ownership structure, on this relationship. Using a sample of 60 French companies for the period 2014-2019, we find new evidence of a reverse causation relationship between accounting conservatism and cross-listing decision in the United States (US). Thus, cross-listed firms in the US are more likely to exhibit more conservative financial reports. In the reverse causality sense, more conservative firms are more likely to cross-list in the US since they can support a higher level of cross-listing costs and satisfy the higher disclosure and governance requirements which allow them to benefit from a better valuation. Our findings also support the new prediction that better governance leads to higher levels of accounting conservatism, implying a mediating impact on the relationship between accounting conservatism and cross-listing decision.
Keywords: 330; Accounting conservatism; cross-listing; board of directors; ownership structure